Determinansi Komponen Permintaan Agregat terhadap Pertumbuhan Ekonomi Regional dan Stabilitas Ekosistem Agribisnis di Kabupaten Deli Serdang: Indonesia - Sakral Puarada; Riris Nadia Syafrilia Gurning; Muhammad Authar ND (Universitas Medan Area, 2026)
This study aims to analyze the dynamics of regional economic growth based on expenditure components and their implications for agribusiness development in Deli Serdang Regency. The study uses a descriptive quantitative approach with simple time series data analysis based on quarterly GRDP data for 2025 sourced from the Central Statistics Agency. The variables analyzed include household consumption, government consumption, gross fixed capital formation (PMTB), and economic growth (GRDP). The results show that Deli Serdang Regency's economic growth is fluctuating with a contraction pattern in the first quarter (-2.84%), recovery in the second-third quarters (1.85% and 2.57%), and stabilization in the fourth quarter (1.19%). Household consumption has proven to be a relatively stable component in supporting economic growth, while government consumption and investment show significant fluctuations. Investment plays a crucial role in driving economic recovery, while government spending has not been fully effective in increasing sustainable economic growth. From an agribusiness perspective, consumption stability reflects consistent demand for food products, while fluctuations in investment and government spending indicate the need to strengthen policies that support sustainable agribusiness development. This study recommends optimizing productive investment and increasing the effectiveness of government spending to strengthen the agribusiness system and regional economic stability.